PENERAPAN MEDIA LAGU RELIGI SEBAGAI UPAYA PENCEGAHAN DAN PENANGANAN PERILAKU BULLYING DI SEKOLAH DASAR - Abd. Rozaq (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
This article aims to describe the application of religious song media as an effort to prevent and address bullying behavior at SD Nurul Faizah Surabaya. A qualitative approach with a case study is used to understand the application of religious songs as a means of prevention and handling of bullying behavior. The research participants consist of students, teachers, and the principal, who are involved in efforts to prevent and address bullying. Data was collected through interviews, observations, and documentation. The findings reveal that the prevention of bullying behavior at SD Nurul Faizah Surabaya is facilitated through the educational media of religious songs, which are sung at the beginning and end of lessons. Addressing bullying behavior at SD Nurul Faizah Surabaya requires the entire school community to manage bullying incidents in accordance with the school's bullying prevention program.